Comparison of Five Advanced Oxidation Processes for Degradation of Pesticide in Aqueous Solution - Augustine Chioma Affam; Malay Chaudhuri; Shamsul Rahman M. Kutty (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
The study compared the technical efficiency and economic cost of five advanced oxidation processes (Fenton, UV photo-Fenton, solar photo-Fenton, UV/TiO2/H2O2 and FeGAC/H2O2) for degradation of the pesticides chlorpyrifos cypermethrin and chlorothalonil in aqueous solution. The highest degradation in terms of COD and TOC removals and improvement of the biodegradability (BOD5/COD ratio) index (BI) were observed to be (i) Fenton - 69.03% (COD), 55.61% (TOC), and 0.35 (BI); (ii) UV photo-Fenton -78.56% (COD), 63.76% (TOC) and 0.38 (BI); (iii) solar photo-Fenton - 74.19% (COD), 58.32% (TOC) and 0.36 (BI); (iv) UV/TiO2/H2O2 - 53.62% (COD), 21.54% (TOC), and 0.26 (BI); and (v) the most technical efficient and cost effective process was FeGAC/H2O2. At an optimum condition (FeGAC 5 g/L, H2O2 100 mg/L, and reaction time of 60 min at pH 3), the COD and TOC removal efficiency were 96.19 and 85.60%, respectively, and the biodegradation index was 0.40. The degradation rate constant and cost were 0.0246 min-1 and 0.74/kg TOC, respectively. The FeGAC/H2O2 process is the most technically efficient and cost effective for pretreatment of the pesticide wastewater before biological treatment.